Acting local, targeting global - João Pompeu (Mètode Science Studies Journal: Annual Review)
High mountain environments, characterized by extreme climates, complex terrain, and socio-environmental challenges, are increasingly vulnerable to global change. Anthropogenic climate change accelerates glacier retreat, snowline shifts, and cryospheric hazards, impacting ecosystems and downstream communities. The Sagarmatha National Park, home to Mount Everest, exemplifies the intersection of climate change, unsustainable tourism, and local environmental degradation. The NeverRest Project addresses these issues by proposing sustainable practices for Everest base camp, encompassing spatial planning, waste management, water and energy use, conservation awareness, and education. By integrating localized action with broader conservation goals, the project offers a replicable model for mitigating climate change and promoting sustainability in high mountain regions globally.